Content Validation of a Version of Oros’ Child Perfectionism Scale Culturally Adapted to the Venezuelan Context - Aguilar Durán, Leonardo Andrés; Castellanos López, Marilyn Yisneida (Pensando Psicología, 2016)
Introduction: Despite its importance, formal, detailed reporting on the content validity of psychometric instruments has often been neglected. In a previous work, the Child Perfectionism Scale by Oros (2003), from Argentina, was linguistically and culturally adapted to the Venezuelan context. Objective: The purpose of this study was to estimate content validity of the Venezuelan version of the above scale through the opinion of judges. Methodology: A group of experts in the field of perfectionism judged whether there is correspondence between what each item of the instrument appears to measure and the dimension to which they belong. To quantify the inter-judge agreement, the so-called Factorial Validity Index (fvi) was used. Results: The total scale and the so-called “Self-Demands”, which refer to perfectionist thoughts, achieved satisfactory indices (fvi > 0.80). There was less agreement with items in the dimension “Reactions to Failure,” partly attributable to cultural differentiation factors influencing emotional expression. Conclusions: Now, the rest of the psychometric validation of the test can be completed. Other studies that pursue an objective similar to that of this work could emulate the procedure presented herein.